Gender differences in responses to an altruistic message regarding rubella vaccination - Okuno, Hideo; Satoh, Hiroshi; Arai, Satoru; Suzuki, Motoi; Kikkawa, Toshiko (Frontiers in Public Health, 2024)
Background: The supplementary immunization activity (SIA) for the rubella vaccination of adult men born between 1962 and 1978 began in 2019 in Japan because of a vaccine gap in the cohort, as vaccination was not mandatory for those born in that period. However, SIA coverage remains low, despite an active campaign and financial support. Methods: We conducted a randomized controlled study based on a 2 (scenario: self-vaccination, child vaccination) × 2 (message: self-interest, group interest) factorial design, using a Japanese online panel. Participants with children were assigned to the child vaccination scenario in Intervention 1, whereas others were assigned to the self-vaccination scenario. After Intervention 1, all participants were given the same information about rubella. In Intervention 2, participants assigned to self-interest messages received a message emphasizing the risk of rubella, and those assigned to group-interest messages received a message emphasizing herd immunity. After Intervention 2, we evaluated the effects using a questionnaire. Results: Among the 2,206 participants, information regarding rubella was evaluated as more reliable in the group-than in the self-interest message condition, especially among women. Women evaluated the necessity of rubella vaccination for adult men and women to be higher in the child-vaccination scenario and group-interest messages. However, no differences were found among men. By contrast, men exposed to the self-interest message positively evaluated the reliability of the rubella explanation. Conclusions: The findings indicate that emphasizing self-interest messages is more effective for men in promoting herd immunity against rubella.